Nordihydroguaiaretic acid enhances the activities of aminoglycosides against methicillin- sensitive and resistant Staphylococcus aureus in vitro and in vivo - Cunningham-Oakes, Edward; Soren, Odel; Moussa, Caroline; Rathor, Getika; Liu, Yingjun; Coates, Anthony; Hu, Yanmin (Frontiers in Microbiology, 2015)
Infections caused by methicillin-sensitive (MSSA) and methicillin-resistant Staphylococcus aureus (MRSA) are prevalent. MRSA infections are difficult to treat and there are no new classes of antibiotics produced to the market to treat infections caused by the resistant bacteria. Therefore, using antibiotic enhancers to rescue existing classes of antibiotics is an attractive strategy. Nordihydroguaiaretic acid (NDGA) is an antioxidant compound found in extracts from plant Larrea Tridentata. It exhibits antimicrobial activity and may target bacterial cell membrane. Combination efficacies of NDGA with many classes of antibiotics were examined by chequerboard method against 200 clinical isolates of MRSA and MSSA. NDGA in combination with gentamicin, neomycin and tobramycin was examined by time-kill assays. The synergistic combinations of NDGA and aminoglycosides were tested in vivo using a murine skin infection model. Calculations of the fractional inhibitory concentration index (FICI) showed that NDGA when combined with gentamicin, neomycin or tobramycin displayed synergistic activities in more than 97% of MSSA and MRSA, respectively. Time kill analysis demonstrated that NDGA significantly augmented the activities of these aminoglycosides against MRSA and MSSA in vitro and in murine skin infection model. The enhanced activity of NDGA resides on its ability to damage bacterial cell membrane leading to accumulation of the antibiotics inside bacterial cells. We demonstrated that NDGA strongly revived the therapeutic potencies of aminoglycosides in vitro and in vivo. This combinational strategy could contribute major clinical implications to treat antibiotic resistant bacterial infections.